The Influence of Public Debate on Political Awareness and Voter Rationality in the Rembang Regional Election - Sellametha Alika Permata Gunaeri; Najwa Fadhilatul Khusna (PT Pro Panoramic Solution, 2025)
Public debate is one of the important means in the democratic process, especially in regional head elections (Pilkada), where the public can directly assess the vision and mission of candidate leaders. In the Rembang Pilkada, public debate played a significant role in increasing public political awareness and influencing voter rationality. This study aims to analyze the impact of public debate on increasing public political understanding and how it influences voters' rational decisions in choosing regional head candidates. The method used in this study is a qualitative approach with in-depth interviews and surveys of a number of voters in Rembang. The results of the study indicate that public debate can increase voter knowledge about political issues and programs of regional head candidates. However, despite the increase in political awareness, many voters still tend to vote based on emotional factors or social identity rather than rational considerations of the quality of the candidate's program. This study suggests the importance of holding more in-depth and informative debates in order to increase voter rationality in choosing regional head candidates.